Effect of Palivizumab Prophylaxis on Respiratory Syncytial Virus Hospitalizations in Preterm Infants Born to 290/7 to 316/7 Weeks of Gestational Age - Zamur, Elifcan; Uygur, Ozgun; Karadag-Oncel, Eda; Gunes, Sezgin; Sahin, Suzan; Kefeli Demirel, Melike; Engur, Defne; Oncel, Mehmet Yekta (Journal of Pediatric Infectious Diseases, 2024)
Objective In 2020, in-line with the recommendations of the Turkish Neonatal Society, a new palivizumab indication was added for preterm infants with 290/7 to 316/7 weeks of gestational age. This study aimed to determine the risk factors of hospitalizations due to lower respiratory tract infections (LRTIs) and respiratory syncytial virus (RSV) in preterm infants (290/7–316/7 weeks of gestational age) who were or were not within the scope of palivizumab indication during the first two RSV seasons (2018–2019 and 2019–2020) and the next two RSV seasons (2020–2021 and 2021–2022) to evaluate the validity of the new indication of palivizumab reimbursement scope.Methods This study was a two-center retrospective and prospective cohort study and included all preterm infants (290/7–316/7 weeks) aged 90 days and younger during the RSV season (October–March). The primary outcome was to compare the hospitalization rates between patients who received palivizumab and those who did not. The secondary outcome was to identify the risk factors for patients hospitalized due to LRTIs.Results Of the 122 preterm infants included in the study, 48.3% (n = 59) were in the prophylaxis group (Group 1) and 51.7% (n = 63) were in the non-prophylaxis group (Group 2). It was noteworthy that 53.8% (n = 14) of the 26 infants hospitalized due to LRTIs were in Group 1 and 46.2% (n = 12) were in Group 2 (p = 0.682). Of the RSV PCR-positive infants, 62.5%(n = 5) were in Group 1 and 37.5% (n = 3) were in Group 2 (p = 0.30). The median length of hospitalization was similar in the groups (p = 0.123).Conclusion The indication for palivizumab prophylaxis can be determined more clearly for our country in light of national multicenter studies with an increased sample size.
Keywords: lower respiratory tract infection; palivizumab; preterm; RSV; infant